Emergency Programming with MIcronutrients in Mind: Evidence on Social Safety Nets - Gilligan, Daniel O. (2020)
Daniel Gilligan POLICY SEMINAR Virtual Event - Micronutrients in emergencies: How can we prevent an increase in hidden hunger? Co-Organized by the Micronutrient Forum and IFPRI JUN 9, 2020 - 09:30 AM TO 10:45 AM EDT